Perfil lipídico sérico de ratos tratados com surfactante - de Castro, Karina Ferreira [UNESP]; Artoni, Silvana Martinez Baraldi [UNESP]; Pacheco, Maria Rita [UNESP] (My University, 2012)
Atherosclerosis is a multifactorial, progressive and slow disease, and hyperlipidaemia is one of the potential factors in the development of atherosclerotic cardiac diseases. The experimental dyslipidaemia carrying out advantages are the production of atheromatous lesions in a short period of time, an adequate dietetic control and environmental factors, the possibility of studies concerning reversibility of atherosclerotic lesions, and pre-clinic experiments with hypolipidaemic substances. This study aims at evaluating tyloxapol analyzing serum lipid levels. Twenty-eight healthy Wistar adults' albino male rats, weighing an average of 200 g were utilized. They were distributed into four experimental groups with seven animals each, as follows: Group I - (control); Group II - treated with tyloxapol at a dose of 500mg/kg of body weight, through intraperitoneal via each 48 hours, for two weeks; Group III - treated with tyloxapol at a dose of 500mg/ kg of body weight, through intraperitoneal via each 48 hours, for three weeks; Group IV - treated with tyloxapol at a dose of 500mg/kg of body weight, through intraperitoneal via each 48 hours, for four weeks. As lipid profile evaluation is concerned, the values of triacylglycerols and HDL have indicated that group III has significantly differed from group I and the values of total cholesterol and LDL have indicated that group I has significantly differed from group II, III and IV. It was concluded that for the studied period the surfactant tyloxapol was effective to inducing hyperlipidaemia.
Serum lipid levels of rats treated with surfactant
Keywords: Cholesterol; Lipid profile; Rat; Surfactant; Triacylglycerol; Animalia; Rattus